2006
DOI: 10.1002/asia.200600256
|View full text |Cite
|
Sign up to set email alerts
|

Titanium and Zirconium Complexes with Non‐Salicylaldimine‐Type Imine–Phenoxy Chelate Ligands: Syntheses, Structures, and Ethylene‐Polymerization Behavior

Abstract: New Ti and Zr complexes that bear imine-phenoxy chelate ligands, [{2,4-di-tBu-6-(RCH=N)-C6H4O}2MCl2] (1: M = Ti, R = Ph; 2: M = Ti, R = C6F5; 3: M = Zr, R = Ph; 4: M = Zr, R = C6F5), were synthesized and investigated as precatalysts for ethylene polymerization. 1H NMR spectroscopy suggests that these complexes exist as mixtures of structural isomers. X-ray crystallographic analysis of the adduct 1HCl reveals that it exists as a zwitterionic complex in which H and Cl are situated in close proximity to one of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 117 publications
1
28
0
Order By: Relevance
“…It should be pointed out that Suzuki and Fujita have reported on a structurally related bis(imine-phenoxy)-Ti complex 28 having a C 6 F 5 on the imine-N with MAO activation, which does not promote living ethyl- 40 Interestingly, DFT calculations have indicated that there is virtually no interaction between the ortho-F and the -H (ortho-F/-H distance 3.66 Å ).…”
Section: Mechanistic Features Of Living Polymerization With Fluorinatmentioning
confidence: 99%
“…It should be pointed out that Suzuki and Fujita have reported on a structurally related bis(imine-phenoxy)-Ti complex 28 having a C 6 F 5 on the imine-N with MAO activation, which does not promote living ethyl- 40 Interestingly, DFT calculations have indicated that there is virtually no interaction between the ortho-F and the -H (ortho-F/-H distance 3.66 Å ).…”
Section: Mechanistic Features Of Living Polymerization With Fluorinatmentioning
confidence: 99%
“…59,67,68 A Ti-FI catalyst in combination with i-Bu 3 Al/ Ph 3 CB(C 6 F 5 ) 4 , which forms a phenoxy-amine Ti complex as a catalytically active species, displays unique behavior for the polymerization of higher a-olefins. Similar reductions are observed for PI and IF catalysts.…”
Section: Stereo-and Regioirregular High-molecular-weight Poly(higher mentioning
confidence: 99%
“…Unique block copolymers created by fluorinated Ti-FI catalysts a Determined by GPC. Interestingly, DFT calculation studies have demonstrated that there is virtually no interaction between the ortho-F and a b-H on the growing polymer chain (ortho-F/b-H distance 3.66 Å ) for 31/MAO catalyst system 68. c Overall propylene (P) or 1-hexene (H) content (mol%): determined by 1 H NMR.…”
mentioning
confidence: 99%
“…Since the ligand structure has a central role in determining the activity as well as the stereospecifity of these types of catalysts, and as shown in Figure 2, flexible electronic nature of a ligand is a key requirement for achieving high activity, the research based on the ligand oriented catalyst design concept has resulted in the discovery of a number of highly active catalysts for the polymerization of ethylene, which include: phenoxy-imine ligand early transition metal complexes (FI catalysts), pyrrolide-imine ligand group 4 transition metal complexes (PI catalysts), indolide-imine ligand Ti complexes (II catalysts), phenoxy-imine ligand group 4 transition metal complexes (IF catalysts), phenoxy-ether ligand Ti complexes (FE catalysts), imine-pyridine ligand late transition metal complexes (IP catalysts), and tris(pyrazolyl) borate ligand Ta complexes (PB catalysts) (Figure 3) [20,[26][27][28][29][30]. In particular, bis(phenoxy-imine) group 4 metal catalysts, developed by Fujita [19][20][21] caused a new revolution in the field of catalytic olefin polymerization.…”
Section: Introductionmentioning
confidence: 99%